T Cell Immunity Evaluation and Immunodominant Epitope T Cell Receptor Identification of Severe Acute Respiratory Syndrome Coronavirus 2 Spike Glycoprotein in COVID-19 Convalescent Patients - Li, Luo; Chen, Qian; Han, Xiaojian; Shen, Meiying; Hu, Chao; Chen, Siyin; Zhang, Jing; Wang, Yingming; Li, Tingting; Huang, Jingjing; Li, Shenglong; Hao, Yanan; et al. (Frontiers in Cell and Developmental Biology, 2021)
A better understanding of the role of T cells in the immune response to Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is helpful not only for vaccine development but also for the treatment of COVID-19 patients. In this study, we determined the existence of SARS-CoV-2-specific T cells in the blood of COVID-19 convalescents. Meanwhile, the specific T cell response in the non-RBD region was stronger than in the RBD region. We also found that SARS-CoV-2 S-specific reactive CD4+ T cells exhibited higher frequency than CD8+ T cells in recovered COVID-19 patients, with greater number of corresponding epitopes presented. Importantly, we isolated the SARS-CoV-2-specific CD4+ T cell receptors (TCRs) and inserted the TCRs into allogenic CD4+ T cells. These TCR-T cells can be activated by SARS-CoV-2 spike peptide and produce IFN-γ in vitro. These results might provide valuable information for the development of vaccines and new therapies against COVID-19.